A review of Russian plankton research in the Gulf of Mexico and the Caribbean Sea in the 1960-1980s - Okolodkov, Yuri B. (HIDROBIOLÓGICA, 2017)
A book, 28 articles and two technical reports were published as results of the Soviet-Cuban and Soviet expeditions in 1962-1984, involving plankton samples collected at about 2,070 stations in the Gulf of Mexico and the Caribbean Sea. The results of those studies remained virtually unknown to the international community because they were published mainly in Russian. Two main types of water circulation in the Gulf resulting from the intensity of the Yucatan Current were distinguished. It was concluded that offshore regions of the Gulf of Mexico and the Caribbean Sea were oligotrophic, the deep-sea regions of the latter being richer in phytoplankton compared to deep-sea areas of the Gulf. Due to the upwellings and runoff from the Mississippi river, the Bank of Campeche, the northwestern Gulf, and the west Florida shelf were characterized by a relatively higher plankton production and by more pronounced seasonal changes in plankton biomass. Cyclonic and anticyclonic horizontal circulations were found to be the main reason for spatial changes in productivity of the Gulf. In various regions, the highest productivity was reported in different seasons, principally in winter on the northern shelf and in summer-autumn on the southern shelf of the Gulf. The annual dynamics of plankton biomass were traced in the Bank of Campeche. In the Caribbean Sea, both the Venezuela shelf and the Honduras continental slope were characterized by their higher productivity. The large amount of data obtained can be used to evaluate long-term changes in biological productivity in the region, species composition, and plankton communities.